2021
DOI: 10.1186/s12968-021-00735-2
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of fast semi-automated left atrial long-axis strain analysis in hypertrophic cardiomyopathy

Abstract: Background The prognostic value of left atrial (LA) size and function in hypertrophic cardiomyopathy (HCM) is well recognized, but LA function is difficult to routinely analyze. Fast LA long-axis strain (LA-LAS) analysis is a novel technique to assess LA function on cine cardiovascular magnetic resonance (CMR). We aimed to assess the association between fast LA-LAS and adverse clinical outcomes in patients with HCM. Methods 359 HCM patients and 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 27 publications
2
14
0
Order By: Relevance
“…During a long follow up-up of 40.9 months, 59 patients with HCM (19.7%) out of 359 experienced the composite endpoint of cardiovascular death, resuscitated cardiac arrest, sudden cardiac death aborted by appropriate ICD discharge, and HF hospital admission. Reservoir and conduit components (HR, 0.94 and 0.89; p = 0.019 and 0.006, respectively) emerged as independent predictors of outcome, also after correcting for the extent of LV fibrosis, confirming the prognostic significance of LA mechanics and expanding the clinical applications of CMR-based myocardial deformation analysis ( 47 ).…”
Section: La Mechanics In Hf Stagesmentioning
confidence: 73%
“…During a long follow up-up of 40.9 months, 59 patients with HCM (19.7%) out of 359 experienced the composite endpoint of cardiovascular death, resuscitated cardiac arrest, sudden cardiac death aborted by appropriate ICD discharge, and HF hospital admission. Reservoir and conduit components (HR, 0.94 and 0.89; p = 0.019 and 0.006, respectively) emerged as independent predictors of outcome, also after correcting for the extent of LV fibrosis, confirming the prognostic significance of LA mechanics and expanding the clinical applications of CMR-based myocardial deformation analysis ( 47 ).…”
Section: La Mechanics In Hf Stagesmentioning
confidence: 73%
“…Compared with the traditional feature-tracking, the fast method demonstrated superior reliability and reproducibility, with a great reduction of analysis time [9]. LA strain derived from this method showed independent prognostic value in ST-segment elevation myocardial infarction and hypertrophic cardiomyopathy [11,12]. Leng et al applied similar method to RA in patients with pulmonary artery hypertension and demonstrated that impaired RA strain reflected RV decompensation and predicted adverse cardiac events [13].…”
Section: Introductionmentioning
confidence: 99%
“…Compared with the traditional feature-tracking, the fast method demonstrated superior reliability and reproducibility, with a great reduction of analysis time [ 9 ]. LA strain derived from this method showed independent prognostic value in ST-segment elevation myocardial infarction and hypertrophic cardiomyopathy [ 11 , 12 ]. Leng et al .…”
Section: Introductionmentioning
confidence: 99%
“…LA strain decrease may signify a severe impairment of atrial compensatory ability [39] , which might account for its great prognostic value in some studies. This predictive usefulness has also been shown in hypertrophic cardiomyopathy, where inadequate LA reservoir strain markedly raised the probability of death and the onset or progression of HF [40,41] . In another study, LA dysfunction by TT was a separate predictor of HF development in the asymptomatic general population [42] .…”
Section: Discussionmentioning
confidence: 74%